2020
DOI: 10.1021/acs.iecr.9b07015
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Pathways in the Phenol/2-Propanol Conversion over the Tandem Raney Ni + ZSM-5 Catalytic System

Abstract: This work investigates the effects of both zeolite accessibility and reaction temperature on the conversion of phenol assisted by 2-propanol over the tandem system Raney Ni + ZSM-5 zeolite. Two different zeolite samples, containing similar SiAl ratios, were used: nanocrystalline ZSM-5 (n-ZSM-5) and hierarchical ZSM-5 (h-ZSM-5), operating at temperatures of 125, 150, and 175 °C. When working with the Raney Ni + n-ZSM-5 system, at low and intermediate temperatures, the main products were mostly benzene and cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…In the last 10 years, various binary catalytic systems based on Raney Ni catalyst have been developed. As given in Table , the solid acid catalysts shifted from ion-exchange resins to more robust zeolites (H-beta and ZSM-5), , and the reaction temperature was decreased from 300 °C to less than 200 °C . High-pressure hydrogen could be also avoided by using methanol ,, or 2-propanol as the hydrogen source.…”
Section: Raney Ni For Biomass Conversionmentioning
confidence: 99%
“…In the last 10 years, various binary catalytic systems based on Raney Ni catalyst have been developed. As given in Table , the solid acid catalysts shifted from ion-exchange resins to more robust zeolites (H-beta and ZSM-5), , and the reaction temperature was decreased from 300 °C to less than 200 °C . High-pressure hydrogen could be also avoided by using methanol ,, or 2-propanol as the hydrogen source.…”
Section: Raney Ni For Biomass Conversionmentioning
confidence: 99%
“…High yields of aromatics (28%) can be obtained at very low Ni loading (0.1 wt.%), and there is no difference in the selectivity of aromatic products when the amount of Ni added is 0.1, 0.5, or 1.0% (Chen et al, 2018 ). The study on effect of reaction temperature on conversion of phenol with hierarchical Ni-ZSM-5 shows that the main products were mostly benzene and cyclohexene formed by phenol deoxygenation at low and intermediate temperatures (393 and 423 K) whereas a shift in the reaction pathways occurred at higher temperature (448 K), leading to high slectivity of valuable alkylphenols (mostly cresols and cyclohexylphenols) generated by the occurrence of alkylation reactions catalyzed by the zeolite acid sites (García-Minguillan et al, 2020 ). The mixture of microporous ZSM-5 and another mesoporous zeolite is also employed for catalytic pyrolysis of biomass.…”
Section: Ni Modified Zsm-5mentioning
confidence: 99%
“…This fact has been recently proved in the hydroconversion of n-alkanes towards branched hydrocarbons over Pt/HZSM-22/Al 2 O 3 catalysts. 38 In a previous study, we reported that the tandem catalytic system RANEY® Ni plus nanocrystalline or hierarchical ZSM-5 39 unveiled alkylation reactions in the phenol conversion alongside the expected reactions (ring saturation, dehydrogenation and dehydration). This alkylation shifted the selectivity towards bulky alkylphenolic products, cresols and cyclo-hexylphenols being the main ones obtained (36% and 17% selectivity respectively over RANEY® Nickel plus hierarchical ZSM-5 at 175 °C).…”
Section: Introductionmentioning
confidence: 95%